Xuexi Daqingren "Sanlao", "Siyan", "Sige Yiyang" de geming zuofeng - Meng Xianchang,
'Study the revolutionary style of the Daqing people's "Three Honests", "Four Stricts" and "Four Equals".' Printno. 8171.2025.